The Role of Image Macros in Online Conversations - Grubišić, Marina (2012)
This paper will attempt to describe the use of image macros in computer-mediated communication, more precisely in conversations that take place in online setting. The Internet is without a doubt a vast social medium as well, and it brings together an astonishingly diverse community of practice that has influenced communication as such thanks to an array of very particular features. Computer-mediated communication has so far enticed research on numerous topics, for instance synchronicity and interactivity, anonymity of users and content, and the degree and relationship of written and oral discourse in this new environment. This relatively new environment offers its users numerous outlets for language creativity and in this presentation we will try to capture and describe one instance of such creativity. Image macros, as used in computer-mediated communication, are pictures with or without additional text that are most often used for humorous effect, and the range of their use has greatly expanded within the online community. Through examples gathered from online conversations we will try to show how image macros are used as valid substitutes for sentences/utterances within a conversation, to what extent the participants have to be introduced to the extralinguistic context they are presented with and how these macros influence textual cohesion of these conversations. Examples are taken from online conversations from eight participants, all native speakers of Croatian and active internet users. A short survey of their overall online activity and attitudes towards language use online is also included. One other important issue will be addressed as well and that is to what extent the extralinguistic context of image macros is present in offline communication, more precisely to what extent this extralinguistic content is context-dependent and relevant. To sum up, this paper will try to describe one specific phenomenon within computer-mediated communication, but it will also try to establish its position within the still dominant realm of offline communication.
Projekt MZOS
ENG